Implementasi Kurilum Merdeka pada Program Sekolah Penggerak Angkatan 3 di TK Pamardisiwi Temanggung - Setya Hartati, Yuni; Luluk Ifadah; Asih Puji Hastuti; Az Zahra Nurul Fida; Dwi Septi Angraeni (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the implementation of the independent curriculum in the 3rd Batch at Early Children Education in Pamardisiwi Kindergarten Temanggung, Central Java. There are three problems that are the main focus of the study, namely: 1). What are the successes and obstacles faced in implementing the independent curriculum ? 2). How is the implementation of the independent curriculum programms? and 3). How is the teaching and learning process ? This research is a field research. The method used is qualitative method. The approach used is phenomenological approach. The study was conducted for a period of two months: from July to August 2024. The results of the study indicate that the curriculum has been implemented well although initially the principal and teachers felt burdened and lacked support from parents. From 13 indicators programms, 11 indicators have been running well and 2 other indicators still need to be improved. The teaching and learning process has been running well. The learning process is carried out centered on students. The conclusion in this study is: the implementation of the curriculum in the early stages has been carried out well overall. However, the institution must improve the implementation of this curriculum towards the developing stage and then to be advanced. Researcher's suggestion: principals, teachers, guardians and all stakeholders must support this activity so that this institution becomes proficient in disseminating IKM to other institutions and what the country aspired in one hundred years of Indonesian independence is achieved in 2045.